Disaccharide compositional analysis of heparan sulfate and heparin polysaccharides using UV or high-sensitivity fluorescence (BODIPY) detection - Skidmore, Mark A; Guimond, Scott E; Dumax-Vorzet, Audrey F; Yates, Edwin A; Turnbull, Jeremy E (Nature protocols, 2010)
One of the first steps in characterizing heparan sulfate (HS) and its close relative heparin is to conduct disaccharide composition analysis. This provides an overall picture of the structure of the polysaccharide in terms of its constituent disaccharides. This is of importance, for example, in the initial characterization of spatially and temporally regulated structures. Two protocols for conducting disaccharide analysis are presented here, both exploiting exhaustive digestion of the polysaccharide, yielding constituent disaccharides, by bacterial heparin lyases. The first method, suitable for microgram quantities of material, relies on the separation of the disaccharides by high-performance liquid chromatography (HPLC) coupled to ultraviolet absorbance detection and can be performed in 2 d. The second exploits reducing end–labeling with the fluorophore BODIPY hydrazide, separation by HPLC, and subsequent fluorescence detection and quantitation. The latter is a high-sensitivity method that requires nanograms of starting material and has a detection limit in the low fmol range, and is thus the most sensitive method for disaccharide compositional analysis of HS yet reported. Fluorescence detection can be routinely carried out in 3 d.